Seeking Help From Police for Intimate Partner Violence: Applying a Relationship Phase Framework to the Exploration of Victims’ Evolving Needs - Shearson, Kim M. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a pervasive social problem requiring multiple levels of intervention across sectors. Women experiencing IPV often seek assistance from police. Such help-seeking efforts are frequently perceived as problematic by both victims and police. A deeper understanding of victims’ needs than is currently evident in the literature is needed to facilitate an appropriate, victim-centered police response across a diverse range of victim presentations. Applying a symbolic interactionist and feminist perspective and guided by a constructivist grounded theory approach, this qualitative study aimed to explore the application of Landenburger’s model of entrapment in and recovery from violent relationships to understand victims’ help-seeking needs when accessing police services. Semistructured interviews were conducted with 16 female victims residing in the culturally diverse Western metropolitan region of Melbourne, Australia. Fourteen victims participated in follow-up interviews. All victims primarily sought to stop the violence and hoped to find a powerful ally in police. Additional help-seeking needs were identified; subtle variations in victims’ aspirations for safety, ego-support, and justice were found across the binding, enduring, disengaging, and recovery relationship phases. Victims progressed from focusing only on the immediate violent event during the binding phase to seeking to maintain long-term safety and exert their rights to protection and freedom from abuse in the recovery phase. While the operational response of police is dependent on level of violence and immediate concerns for victims’ physical safety, victims’ help-seeking aims are very much contingent upon their relationship phase and the associated strategies for managing the violence they use. In particular, this study provides insight into the needs of women in the enduring relationship phase, when factors such as diminished agency and low expectations of legal protection were found to constrain victims’ help-seeking aspirations, sometimes eventuating in a cycle of chronic police intervention.